Roles of PKC and phospho‑adducin in transepithelial fluid secretion by Malpighian tubules of the yellow fever mosquito - Miyauchi, Jeremy T. (Landes Bioscience, 2013)
The diuretic hormone aedeskinin‑III is known to increase the paracellular Cl(-) conductance in Malpighian (renal) tubules of the mosquito Aedes aegypti via a G protein-coupled receptor. The increase serves the blood-meal-initiated diuresis and is associated with elevated levels of Ca(2+) and phosphorylated adducin in the cytosol of tubule. In the present study we have cloned adducin in Aedes Malpighian tubules and investigated its physiological roles. Immunolabeling experiments are consistent with the association of adducin with the cortical cytoskeleton, especially near the apical brush border of the tubule. An antibody against phosphorylated adducin revealed the transient phosphorylation of adducin 2 min after stimulating tubules with aedeskinin‑III. The PKC inhibitor bisindolylmaleimide‑I blocked the phosphorylation of adducin as well as the electrophysiological and diuretic effects of aedeskinin‑III. Bisindolylmaleimide‑I also inhibited fluid secretion in control tubules. Phorbol 12‑myristate 13‑acetate increased phosphorylated adducin levels in Malpighian tubules, but it inhibited fluid secretion. Thus, the phosphorylation of adducin by PKC alone is insufficient to trigger diuretic rates of fluid secretion; elevated levels of intracellular Ca(2+) may also be required. The above results suggest that the phosphorylation of adducin, which is known to destabilize the cytoskeleton, may (1) facilitate the traffic of transporters into the apical brush border supporting diuretic rates of cation secretion and (2) destabilize proteins in the septate junction thereby enabling paracellular anion (Cl(‑)) secretion at diuretic rates. Moreover, PKC and the phosphorylation of adducin play a central role in control and diuretic tubules, consistent with the dynamic behavior of both transcellular and paracellular transport pathways.